Influence of Intrinsic Aerobic Exercise Capacity and Sex on Cardiac Injury Following Acute Myocardial Ischemia and Reperfusion - Alsahly, Musaad B.; Zakari, Madaniah O.; Koch, Lauren G.; Britton, Steven; Katwa, Laxmansa C.; Lust, Robert M. (Frontiers in Cardiovascular Medicine, 2021)
Purpose: Previous reports have suggested that active exercise aside, intrinsic aerobic running capacity (Low = LCR, high = HCR) in otherwise sedentary animals may influence several cardiovascular health-related indicators. Relative to the HCR phenotype, the LCR phenotype is characterized by decreased endothelial reactivity, increased susceptibility to reperfusion-induced arrhythmias following short, non-infarction ischemia, and increased diet-induced insulin resistance. More broadly, the LCR phenotype has come to be characterized as a “disease prone” model, with the HCRs as “disease resistant.” Whether these effects extend to injury outcomes in an overt infarction or whether the effects are gender specific is not known. This study was designed to determine whether HCR/LCR phenotypic differences would be evident in injury responses to acute myocardial ischemia-reperfusion injury (AIR), measured as infarct size and to determine whether sex differences in infarction size were preserved with phenotypic selection. Methods: Regional myocardial AIR was induced in vivo by either 15 or 30 min ligation of the left anterior descending coronary artery, followed by 2 h of reperfusion. Global ischemia was induced in isolated hearts ex vivo using a Langendorff perfusion system and cessation of perfusion for either 15 or 30 min followed by 2 h of reperfusion. Infarct size was determined using 2, 3, 5–triphenyltetrazolium chloride (TTC) staining, and normalized to area at risk in the regional model, or whole heart in the global model. Portions of the tissue were paraffin embedded for H&E staining and histology analysis. Results: Phenotype dependent differences in infarct size were seen with 15 min occlusion/2 h reperfusion (LCR > HCR, p < 0.05) in both regional and global models. In both models, longer occlusion times (30 min/2 h) produced significantly larger infarctions in both phenotypes, but phenotypic differences were no longer present (LCR vs. HCR, p = n.s.). Sex differences in infarct size were present in each phenotype (LCR male > LCR female, p < 0.05; HCR male > HCR female, p < 0.05 regardless of length of occlusion, or ischemia model. Conclusions: There is cardioprotection afforded by high intrinsic aerobic capacity, but it is not infinite/continuous, and may be overcome with sufficient injury burden. Phenotypic selection based on endurance running capacity preserved sex differences in response to both short and longer term coronary occlusive challenges. Outcomes could not be associated with differences in system characteristics such as circulating inflammatory mediators or autonomic nervous system influences, as similar phenotypic injury patterns were seen in vivo, and in isolated crystalloid perfused heart ex vivo.